Psychology research in the Philippines observations and prospects.[article]. - Bernardo, Allan B. I.
The paper is an attempt to take stock of the state of psychology research in the Philippines. In particular it seeks to describe the research culture, the problems, and opportunities characteristic of it. To provide a stimulus for this assessment a survey of psychology publications was undertaken. The results of the survey were used as a springboard for making observations about substantive concerns and level of analysis of psychology research in the country. The paper traces limitations of psychology research to the lack of a real research culture and identifies some opportunities that could lead to the development of such. The paper ends with some recommendations regarding how psychology research can grow and play a more important role in the life of our nation.